2015
DOI: 10.1242/jcs.163063
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt receptor Frizzled-4 modulates ADAM13 metalloprotease activity

Abstract: BSTRACTCranial neural crest (CNC) cells are a transient population of stem cells that originate at the border of the neural plate and the epidermis, and migrate ventrally to contribute to most of the facial structures including bones, cartilage, muscles and ganglia. ADAM13 is a cell surface metalloprotease that is essential for CNC cell migration. Here, we show in Xenopus laevis embryos that the Wnt receptor Fz4 binds to the cysteine-rich domain of ADAM13 and negatively regulates its proteolytic activity in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Instead, ADAMs 10 and 17, two somatic ADAMs, are known to interact with tetraspanins and nonproteolytic members of the Rhomboid family (iRhoms), respectively, which regulate the trafficking, stability and activity of these ADAMs (Adrain et al, 2012;Dornier et al, 2012;Haining et al, 2012;Matthews et al, 2017;McIlwain et al, 2012). The activity of Xenopus ADAM13 has also been shown to be regulated by other proteins, such as PACSIN2 and XFz4 (Abbruzzese et al, 2015;Cousin et al, 2000). In the current study, we observed a protective effect of ADAM19 towards ADAM13, which underlies the in vivo function of ADAM19 in NC specification.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, ADAMs 10 and 17, two somatic ADAMs, are known to interact with tetraspanins and nonproteolytic members of the Rhomboid family (iRhoms), respectively, which regulate the trafficking, stability and activity of these ADAMs (Adrain et al, 2012;Dornier et al, 2012;Haining et al, 2012;Matthews et al, 2017;McIlwain et al, 2012). The activity of Xenopus ADAM13 has also been shown to be regulated by other proteins, such as PACSIN2 and XFz4 (Abbruzzese et al, 2015;Cousin et al, 2000). In the current study, we observed a protective effect of ADAM19 towards ADAM13, which underlies the in vivo function of ADAM19 in NC specification.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our result also suggests that when CIL needs to be reduced, for example to invade tissues that may express cadherin-11, ADAM13 can perform this function rapidly. Given that the proteolytic activity of ADAM13 is inhibited by Fz4 in the CNC (Abbruzzese et al, 2015), this protein could act as a switch to control cadherin-11 cleavage at various phases of CNC development and as such finely tune the intensity of CIL.…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were transcribed in vitro into mRNA according to manufacturer's description (Ambion Inc.). in vivo CNC migration assays by targeted injection of a fluorescent lineage tracer were performed as previously published (Abbruzzese et al, 2014; Abbruzzese et al, 2015; Cousin et al, 2011; Cousin et al, 2012). Eight-cell stage embryos were injected into the D1 blastomere with 333 pg of RFP-flag mRNA, plus 333 pg of all cadherin-11 constructs for overexpression assays.…”
Section: Methodsmentioning
confidence: 99%
“…Of the frizzled receptor family members, frizzled-4 has previously been shown to be of particular interest with respect to its role in the regulation of stem cell maintenance, neuroprotection, and cell migration in the CNS [ 19 21 ]. In the present study, we examined the expression of this Wnt receptor in the enteric nervous system of infants by immunohistochemistry, RT-PCR, and flow cytometry analysis.…”
Section: Introductionmentioning
confidence: 99%